Saint Vincent and the Grenadines. Significant achievements 2010-2017 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in Saint Vincent and the Grenadines are identified, during the period from 2010 to 2017, with respect to the needs and interests of the country, strengthening issues such as biosafety, good agricultural practices, risk management , water management, soil management, resilience against climate change, agribusiness, health and food safety. Likewise, technical assistance was provided to women for their inclusion in agriculture. Finally, work was done to improve the value chains of vegetables, poultry and pigs, in addition to the control of animal diseases.